STUDI PERBANDINGAN PENGEMBANGAN LAYANAN PAUD DI KECAMATAN BREBES DAN DI KECAMATAN BULAKAMBA KABUPATEN BREBES (Universitas Negeri Semarang, 2013)
Based on data obtained by the Education Department in Brebes Regency, 128 early child education (PAUD) have been established in the Brebes district area. There are consist of 37 kindergarten ( TK),35 playgroups (KB),2 parenting group (TPA) ,and 43 (satuan PAUD sejenis) while in Bulakamba District there are 86 (early child education) availabl e. Consist of : 20 kindergartens (TK), 23 play groups (KB), 43 (satuan paud sejenis), and parenting groups is not available. The objectives of this research are: (1) To determine the profile of the development of th e early child education (PAUD) in the Brebes and Bulakamba district area. (2) To understand the obstacles faced by brebes and bulakamba district area in the development of early child education (PAUD) services. (3) to det ermine the steps taken by brebes and bulakamba district areas in order to develop early child education services. This research is using a qualitative method. This research is located in Brebes and Bulakamba district. T he data are collected by the interview, observation, and documentary. Validity check of this research is using a triangulation source (UPTD education, chief of HIMPAUDI, chief of IGKTI, and chief of IGRA). Data collected and analyzed using the i nteractive model as if offered by (Miles and Huberman) through: (1) collecting data; (2) presenting data (3) and conclusion ( verification) In order to obtain valid and relevant data.Results of this research are : 1) there are differentiation available i n the form of PAUD services. In Brebes district, there are 4 forms of PAUDÂ ervices, they are TK,RA,KB, and TPA, whereas in Bulakamba districtÂ there are 3 forms of PAUD service, there are TK,RA, and KB, but in both districts there is no SPS available. 2) the obstacles faced by both districts in order to develop PAUD services is the financial aspect. Less of incentives for the t eachers/tutor , and academic qualification of teacher is less as the government qualification. 3) the steps taken by Brebes and Bulakamba districts in order to develop PAUD services is by giving a financial support such as BOP,APBN,A PBD. Based on that conclusion, is advisable to : (1) The Department of Education and UPTD Brebes, is expected to further improve the system of education funding distribution. (2) IGTKI, IGRA, and HIMPAUDI expec ted to conduct trainings and seminars for administrators and educators that early childhood education can completely managed and develop optimally.